1998
DOI: 10.1165/ajrcmb.18.2.2803m
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinnervation of the Airways in Transgenic Mice Overexpressing Nerve Growth Factor

Abstract: Neuropeptides released from sensory nerve endings are potential mediators of airway inflammation in asthma and lung injury induced by inhalation of respiratory irritants. To develop an in vivo model for assessing the contribution of neurogenic inflammation in these processes, we have generated transgenic mice with altered innervation of the lung. To generate mice with an increased innervation of the airways, we placed the gene that encodes nerve growth factor (NGF) under control of the lung-specific Clara-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(157 citation statements)
references
References 55 publications
4
152
0
1
Order By: Relevance
“…The p75 low anity NGF receptor is also shown to be responsible for an upregulation in tachykinin content in sensory nerves (Lee et al, 1992). Hoyle et al (1998) showed that transgenic mice over-expressing NGF in the airways develop a hyperinnervation of the airways and an increase in substance P. Other studies reported that long-term NGF exposure induces upregulation of substance P in sensory nerves, though this was not studied in the airways (e.g. Lindsay & Harmar, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The p75 low anity NGF receptor is also shown to be responsible for an upregulation in tachykinin content in sensory nerves (Lee et al, 1992). Hoyle et al (1998) showed that transgenic mice over-expressing NGF in the airways develop a hyperinnervation of the airways and an increase in substance P. Other studies reported that long-term NGF exposure induces upregulation of substance P in sensory nerves, though this was not studied in the airways (e.g. Lindsay & Harmar, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, NGF activates the TrkA receptor to induce migration of pulmonary fibroblasts (Kohyama et al, 2002) and regulation of extracellular matrix synthesis (Khan et al, 2002;Takahashi et al, 2000). These results therefore suggest a role for the TrkA receptor in NGF-induced airway sub-epithelial fibrosis in vivo (Hoyle et al, 1998). We also reported that NGF induces proliferation of the airway smooth muscle through activation of the TrkA receptor and may therefore participate to hyperplasia of the smooth muscle layer in vivo (Freund-Michel et al, 2006).…”
Section: Ngf Trka and Tissue Remodelling 531 Asthmamentioning
confidence: 97%
“…NGF also displays its role of growth factor on airway nerves, in particular on sensory airway nerves (Hoyle et al, 1998), and is able to stimulate other airway structural cells such as pulmonary fibroblasts or airway smooth muscle cells (Freund-Michel & Frossard, 2008a). Some of these effects involve activation of the TrkA receptor expressed on these cells (Fig.…”
Section: Ngf Effects In the Lung Mediated By Activation Of The Trka Rmentioning
confidence: 99%
“…As evidenced from animal studies, NGF may contribute to the development of airway hyperresponsiveness [3 -5] and to an increased sensory and sympathetic innervation in the lung [4], and it may evoke a phenotypic change of airway sensory neurones [4]. NGF also has a profound effect on cells of the immune system, many of which are critically important in the development of pulmonary inflammation and asthma-related symptoms.…”
mentioning
confidence: 99%